Pengaruh Content Marketing dan Online Customer Review di TikTok Terhadap Keputusan Pembelian Produk Sabun Cuci Muka Garnier. - Nabila Ayu Kristina; Siti Aminah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Technology that is growing rapidly, especially in the field of social media, provides many opportunities forbusiness people as a marketing medium for company products so that they can be recognized by the wider community, one of which is the TikTok application. The purpose of this study is to find out whether content marketing and online customer reviews on TikTok influence the purchasing decision of Garnier face wash products. The research sample consisted of UPN Veterans East Java students who have a TikTok account and havepurchased Garnier face wash, a total of 72 respondents, using a purposive sampling method. Data collection method used is a questionnaire. There were 72 respondents who were then analyzed using Partial Least Square (PLS). The results of this study indicate that content marketing has a positive influence on purchasing decisions and online customer reviews also have a positive influence on purchasing decisions. Keywords: Content Marketing; Online customer reviews; Buying decision.